2018
DOI: 10.1055/s-0038-1669902
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Reconstruction Using Bone-Patellar Tendon-Bone Autograft with Remnant Preservation: Comparison of Outcomes According to the Amount of Remnant Tissue

Abstract: There has been controversy about whether remnant tissue of anterior cruciate ligament (ACL) has to be preserved in ACL reconstruction. The purpose of the study was to compare clinical outcomes between groups of patients who underwent ACL reconstruction with bone-patellar tendon-bone (BPTB) autograft divided according to amount of ACL remnant and investigate effect of remnant preservation on outcomes of ACL reconstruction. A total of 185 patients who underwent ACL reconstruction with BPTB autograft were retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Remnant preservation is beneficial in preserving proprioception of the native ACL and graft maturation, including synovialization, and the amount of preserved remnant is known as the important factor. 4,5,9,12,29,30 Although our study did not show a significant difference in graft maturation on follow-up MRI, this method preserved more remnant and provided better coverage, as in the previous studies. 5,21…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Remnant preservation is beneficial in preserving proprioception of the native ACL and graft maturation, including synovialization, and the amount of preserved remnant is known as the important factor. 4,5,9,12,29,30 Although our study did not show a significant difference in graft maturation on follow-up MRI, this method preserved more remnant and provided better coverage, as in the previous studies. 5,21…”
Section: Discussionsupporting
confidence: 52%
“…4,16,19,28 However, recent reports including meta-analyses showed a better clinical outcome. 7,9,13,14,21 Our current study showed a statistically significant difference in IKDC subjective score. In the Lysholm and HSS scores, although there was no significant difference, the mean scores were better in group R. Considering the ceiling effect of the Lysholm and HSS scores, our current study demonstrated that remnant preservation with tensioning was better than the classical method regarding clinical outcome.…”
Section: Discussionsupporting
confidence: 49%
“…Remnant-preserved ACL reconstruction is gaining popularity because the remnant-preservation effect may have the advantages of synovial coverage of the graft, graft remodeling, proprioceptive recovery, stability, and better clinical outcomes, [14][15][16]29 although controversial reports exist. 30,31 However, most remnant-preserved ACL reconstructions do not repair the remnant.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, remnant-preserved anterior cruciate ligament (ACL) reconstruction has gained popularity because the remnant-preservation effect may be advantageous for graft remodeling, proprioceptive recovery, and clinical outcomes. [14][15][16] We describe the technique of anatomical arthroscopic ATFL repair and reconstruction (AAARR) using a free tendon graft, which has the possible advantages of not only remnant preservation but also sharing of the ligament load by the repaired ATFL remnant and the reconstructed ATFL graft. A summary of the key steps is provided in Table 1, and a summary of the technique is shown in Video 1.…”
mentioning
confidence: 99%
“…The amount of remnant ACL tissue was graded as 0 (no remnant), I (remnant <1/3), II (remnant of 1/3 to 2/3), and III (remnant >2/3) according to the length proportion covering the reconstructed ACL. 21 The hip–knee–ankle angle was measured on the preoperative weightbearing whole–leg radiograph. 14 The posterior tibial slopes were measured on preoperative MRI.…”
Section: Methodsmentioning
confidence: 99%